آليات المنهج الاجتماعي في سورة يوسف دراسة لغوية اجتماعية - Elassali, Fatima Ezzahraa (Kalimatuna: Journal of Arabic Research, 2024)
The study aims to provide an applied study of the mechanisms of the social curriculum using the religious text "Surah Youssef/Yusuf" as a model, with guiding considerations respecting the specificity and sanctity of the Koranic text, to provide a clear understanding of the story of Joseph "Allah peace" in the Holy Koran and to highlight its social semantics. The research also aims to learn about the social classes in "Yusuf Hizbul Peace" society, as well as the many types of caste conflict and its impact on Egyptian society. The study’s findings demonstrated the efficiency of using the social curriculum to highlight the unique characteristics of Egyptian society: their behaviors, values, and social phenomena, and providing logical analytical interpretations of the character's behavior in the story "Yusuf Alayhi al-Salam." Focusing on the linguistic part of the word revealed social connotations that highlighted the meaning and orientation of speech since it contains a variety of social values related to religion, culture, morals, and humans.